Does Extraversion, Agreeableness and Collectivism Leverage Levels for Job Involvement? - Rusdi, Muhammad; Tjahjono, Heru Kurnianto (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2023)
Job involvement is crucial to worker performance and productivity. This paper investigates the effects of extraversion and agreeableness on job involvement. We also suggest a link between collectivism and job involvement. The data were submitted by 190 registered nurses who worked at two public hospitals for additional research by employing PLS-SEM analysis. The findings show that extraversion, agreeableness, collectivism, and employee job involvement are all positively correlated. We consider the study's practical implications and conclude that personality traits can affect job involvement.